Technology Of Wool Fiber Washing and Oil Removal - O.A. Toshbekov; I.A. Nabiyeva; M.K. Urozov; D.A. Alikulova; S.A. Xolmurodova (Zien Journals, 2021)
The composition of the washing solution consists of surfactant and soda. Under the influence of soda, the residual fat-wax substances in the fiber become soluble, and the surfactant emulsifies the fatwax substances that have passed into this soluble state, ensuring their release from the fiber
Keywords: Washing; Fiber; Return Cooler; Glass Cartridge Case